DNA damage and shell malformation in Blue Mussel, Mytilus edulis - Khusnul Yaqin (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
Pollutants in waters that cause DNA damage, such as tributyltin, have been known to cause malformations in the mussel shell, which need attention to be studied. Shell malformations or deformities of blue mussels were observed in Norsminde Fjord harbour. The mean shell thickness index of blue mussels from the polluted site was greater than it from expected clean waters. DNA damages detected using the versatile comet assay which expressed as tail length and olive tail moment were evaluated in blue mussels gill cells both in situ and in vitro. The results showed that the average of DNA damages in treatments, namely the polluted site, tributyltin chloride (TBTC) (10 g/l), and hydrogen peroxide (H2O2) (10 M) were different from the expected unpolluted site. Although comet assay is considered as an unspecific assay, the results proposed the similarity of DNA damage character of blue mussel gill cells when exposed to tributyltin chloride and taken directly from the polluted site. The data obtained are important for assessing the environmental risks created by genotoxic agents, e.g. tributyltin, used as antifouling agents in marine paints.